The Effects of Socioeconomic Status on Health Behaviors and Outcomes Among Adolescents - Rizky Aditya; Fitri Amalia (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This study investigates the influence of socioeconomic status (SES) on health behaviors and outcomes among Indonesian adolescents. Using data from schools across regions with varied socio-economic profiles, the research examines how income, education, and family stability affect physical activity, dietary habits, and mental health in adolescents. Results reveal that lower SES is associated with unhealthy behaviors and poorer health outcomes, such as reduced physical activity, imbalanced diets, and higher levels of stress. These findings suggest a pressing need for tailored interventions in low-income areas to improve adolescent health outcomes.